2009
DOI: 10.1111/j.1469-8749.2009.03306.x
|View full text |Cite|
|
Sign up to set email alerts
|

Sensory and motor deficits in children with cerebral palsy born preterm correlate with diffusion tensor imaging abnormalities in thalamocortical pathways

Abstract: Aim  Cerebral palsy (CP) is frequently linked to white matter injury in children born preterm. Diffusion tensor imaging (DTI) is a powerful technique providing precise identification of white matter microstructure. We investigated the relationship between DTI‐observed thalamocortical (posterior thalamic radiation) injury, motor (corticospinal tract) injury, and sensorimotor function. Method  Twenty‐eight children born preterm (16 males, 12 females; mean age 5y 10mo, SD 2y 6mo, range 16mo–13y; mean gestational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
277
3
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(305 citation statements)
references
References 33 publications
15
277
3
5
Order By: Relevance
“…DTI carries unique anatomical information that cannot be obtained by relaxation-based contrasts and prior studies have demonstrated the usefulness of evaluating the correlation between white matter damage and clinical function in preterm infants and spastic CP patients (11)(12)(13)(14)(15)(16)(17). Previously, manual-ROI based analyses of DTI data, including ours, have been reported for CP patients (11)(12)(13)(14)(15)(16)(17), which have indicated more diffuse and severe involvement of the deep gray matter and white matter structures in athetotic CP patients compared to the spastic type. These analyses, however, measured only a small portion of the brains, leaving many brain structures unmeasured.…”
Section: Introductionmentioning
confidence: 99%
“…DTI carries unique anatomical information that cannot be obtained by relaxation-based contrasts and prior studies have demonstrated the usefulness of evaluating the correlation between white matter damage and clinical function in preterm infants and spastic CP patients (11)(12)(13)(14)(15)(16)(17). Previously, manual-ROI based analyses of DTI data, including ours, have been reported for CP patients (11)(12)(13)(14)(15)(16)(17), which have indicated more diffuse and severe involvement of the deep gray matter and white matter structures in athetotic CP patients compared to the spastic type. These analyses, however, measured only a small portion of the brains, leaving many brain structures unmeasured.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have used DTI and tractography for the assessment of white matter injury in neonates, 16,17 and most tractography studies were performed on children older than 2 years of age and usually in a small cohort. [18][19][20] Little is known about the microstructural changes in specific fiber tracts in the preterm brain at term-equivalent age, and to our knowledge, no study has yet shown the association between microstructural changes by fiber tracking and WMA graded according to Woodward et al 11 In this study by using DTI and probabilistic tractography, we investigated DTI parameters (tract volume, FA, MD, // , and Ќ ) in the CST, SLF, TRs, and corpus callosum. The aim of the study was to investigate whether WMA on conventional brain MR imaging are related to diffusion changes in specific fiber tracts.…”
mentioning
confidence: 98%
“…[14][15][16] In addition, correlations have been shown between diffusion measures in motor and sensory tracts and specific measures of sensory and/or motor functions. [5][6][7][17][18][19][20] Some studies suggest that sensory and motor functions correlate more strongly with changes in the sensory pathways (superior and posterior thalamic radiation) than changes in the motor pathways (CST). 6,19 These findings indicate that preservation of sensory pathways is important for motor function.…”
mentioning
confidence: 99%
“…[5][6][7][17][18][19][20] Some studies suggest that sensory and motor functions correlate more strongly with changes in the sensory pathways (superior and posterior thalamic radiation) than changes in the motor pathways (CST). 6,19 These findings indicate that preservation of sensory pathways is important for motor function. However, most tractography studies in CP have used deterministic diffusion tensor tractography, which is a limitation because the algorithm cannot progress in areas where the tensor model shows a high uncertainty in the estimated fiber directions due to complex fiber architecture or pathologic changes.…”
mentioning
confidence: 99%